Australian University Approaches to Indigenous Policy - Gunstone, Andrew (The Australian Journal of Indigenous Education, 2008)
Abstract In this paper, I discuss several key issues – governance, employment, research, culture, anti-racism policies, curriculum, student support and student success – that are critically important in enabling universities to meet the educational needs of Indigenous peoples. I also analyse a representative sample of Australian universities and argue that Australian universities have generally failed to adequately address these key issues. Further, I compare this study to a similar study that I conducted in 2000 and analyse any similarities and differences between the two studies.